From Distinction to Lifestyling: The Practices of Urban Women Midlife Consuming Popular Anti-Aging Skincare - Radius Setiyawan; Sri Lestari (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2020)
Due to anti-aging popular products, people, especially urban women, can now delay aging. It changes the concept of aging and also influences how urban women think and act. This article examines the practices of middle-aged women, how they perceive using popular and trending anti-aging skincare, what motivated them to do so, and how women try not to grow old with specific goals. We interviewed ten women in urban areas, classified as midlife women aged 35 years and over. They comprised varied professions, classes, economic status, regional identity, age, and anti-aging products and brands. Interviews were unstructured to provide multiple opportunities and allow participants to talk flexibly about their practices and experiences using their own words. The findings indicated that there was a practice of life styling, namely behavior that merely demonstrated a particular lifestyle without being supported by economic capacity, which was the basis of actual consumption. Lower middle-class women demonstrated these practices, while the upper-class women's habits provided no less exciting insights. They consume anti-aging skin care for distinction purposes, as a practice of distinguishing oneself from others regarding appearance, social class, and identity.